COMMON TRANSLATION PROBLEMS OF SET EXPRESSIONS (Лучшие интеллектуальные исследования, 2025)
Abstract: This article examines the common challenges involved in translating set expressions, including idioms, proverbs, collocations, and phrasal verbs. It highlights the linguistic and cultural complexities that make direct translation difficult, such as the lack of direct equivalents, cultural specificity, structural differences, and the risk of losing figurative meaning. The study draws on examples from English and Uzbek to illustrate these challenges and explores practical strategies for overcoming them, including functional equivalence, descriptive paraphrase, and cultural substitution. The findings underscore the importance of cultural awareness and context-sensitive approaches in achieving accurate and meaningful translations.